The Impact of Life Story Writing on Insecurity in University Students Living with Foster Parents - Adolfina Oualeng; Halena Muna Bekata; Agnes M. Kolly; Melkiasar Penmaley (Universitas PGRI Yogyakarta, 2026)
This study aims to examine the impact of life story writing on feelings of insecurity among college students who had been temporarily placed with foster parents. Using a qualitative, hermeneutic-phenomenological approach, data were collected through individual counseling with nine students who reported insecurity. The narratives written by participants served as a reflective space for exploring past wounds, alleviating emotional burdens, and forming new understandings of themselves. The results show that writing a life story facilitates self-awareness, uncovers harmful defense mechanisms, and encourages the creation of new meanings from painful experiences. There is a shift from a trauma-centered narrative to a resilience-centered narrative, recognizing self-worth, fostering hope, and building a positive identity. Spiritual dimensions also emerged as a source of strength in making sense of adversity. Thus, life story writing is an effective intervention for helping students manage insecurity and strengthen their psychosocial resilience. Keywords: life story, insecurity, counseling, foster parents